Genetic heterogeneity of uncharacterized childhood autoimmune diseases with lymphoproliferation. Issue 2 (29th September 2017) - Takagi, Masatoshi; Hoshino, Akihiro; Yoshida, Kenichi; Ueno, Hiroo; Imai, Kohsuke; Piao, Jinhua; Kanegane, Hirokazu; Yamashita, Motoi; Okano, Tsubasa; Muramatsu, Hideki; Okuno, Yusuke; Shiraishi, Yuichi; et al.
Abstract: Autoimmune diseases in children are rare and can be difficult to diagnose. Single causative genes have been identified for some pediatric autoimmune diseases. Such orphan diseases may not be diagnosed properly due to the variability of patients' phenotypes. Guidelines for the diagnostic process need to be developed. Fifteen patients with uncharacterized childhood autoimmune diseases with lymphoproliferation that had negative testing for autoimmune lymphoproliferative syndrome were subjected to whole‐exome sequencing to identify genes associated with these conditions. Five causative genes, CTLA4, STAT3, TNFAIP3, IKZF1, and PSTPIP1, were identified. These genes should be considered as candidates for uncharacterized childhood autoimmune diseases with lymphoproliferation.